Where Does the Money Come From? Humanizing High Socioeconomic Status Groups Undermines Attitudes Toward Redistribution - Sainz, Mario; Martínez, Rocío; Rodríguez-Bailón, Rosa; Moya, Miguel (Frontiers in Psychology, 2019)
The concentration of wealth in the hands of a few at the expense of general impoverishment is a major problem in some modern societies. However, there is a general opposition to redistribution policies or to the application of a progressive taxation system. The goal of this research was to explore one factor that might drive the attitudes toward income redistribution: The (de)humanization of high socioeconomic status groups. Previous studies have shown that high socioeconomic status groups tend to be considered as unemotional machines without any concern for others. However, the consequences of mechanizing (vs. humanizing) high socioeconomic status on the interpretation of socioeconomic differences has not been explored yet. We considered that humanizing high socioeconomic status groups might have an unexpected negative effect on attitudes about income inequality and wealth concentration. Specifically, this research aims to determine how humanizing high socioeconomic status groups influences people’s perceptions of the group’s wealth and preferences for income redistribution. We conducted two studies in which we manipulated the humanity (mechanized vs. humanized in terms of their Human Nature traits) of a high socioeconomic status group. Results of these two studies showed that humanizing (vs. mechanizing) high socioeconomic status groups led to lower support for income redistribution/taxation of wealthy groups, through considering that the group’s wealth comes from internal sources (e.g., ambition) rather than external ones (e.g., corruption). These results were independent of the group’s likeability and perceived competence/warmth. The present research provides valuable insight about the possible dark side of humanizing high socioeconomic status groups as a process that could contribute to the maintenance of the status quo and the legitimation of income inequality in our societies.